“Will Active Learning Experience Make You Better?” The Effect of Active Learning on Generation Z’s Self-Efficacy, Self-Esteem, and Food Choice Wiseness at School - Habibie, Marini Putri Ayu; Soesilo, Primidya Kartika Miranda (Journal of Social Research, 2023)
Reaching the age of adolescence, children need sufficient nutrients to grow rightly. Nevertheless, dietary habit in children has been extensively found to be ill-considered as many of them have not been able to distinguish nutritional ingredients in food. Mastering nutrition and growing a habit of healthy eating is imperative regarding their better future. This research aimed to examine whether a particular learning method (active vs. passive) would lead to wiser food choices, better self-efficacy, and higher self-esteem. The study case took the secondary students in LabSchool, Jakarta in 2018. Experimental research with a factorial design is employed in the research design. The experiment involved 227 samples of Generation Z. One group was assigned to a hands-on cooking class model (active learning) while the other half as the control group was assigned to a cooking demonstration (passive learning) class model. The result of this research implied that students who are exposed to hands-on cooking classes (active learning) show a healthier shift in their wiseness towards preferring healthy food. The limitation of the study was time and resources. It is suggested in that the future the researcher may extend the experiment’s duration and give more variations of samples to comprehend larger knowledge.